2020
DOI: 10.2147/cmar.s257188
|View full text |Cite
|
Sign up to set email alerts
|

<p>A Review About Pembrolizumab in First-Line Treatment of Advanced NSCLC: Focus on KEYNOTE Studies</p>

Abstract: Lung cancer is currently the malignant tumor with the highest incidence and mortality in the world, while non-small cell lung cancer (NSCLC) is the most common pathological type of lung caner. In the past few decades, the only treatment options available for advanced NSCLC patients have been targeted therapy or chemotherapy, but these therapies are inevitably tolerated by tumors. The discovery of immune checkpints that mediate the immune escape of tumor cells have been promoting a series of immune checkpoint i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 124 publications
(132 reference statements)
0
26
0
1
Order By: Relevance
“…In addition to pembrolizumab and atezolizumab, which were developed by multinational corporations (55,56), three locally developed PD-1 inhibitors (camrelizumab, tislelizumab, and sintilimab) are also available in China (31,48,(57)(58)(59). 2) (9,67,68). Some of the trials were conducted only in China, and some were international multicenter clinical trials that involved Chinese sites (69).…”
Section: Current Nsclc Immunotherapy Landscapementioning
confidence: 99%
See 3 more Smart Citations
“…In addition to pembrolizumab and atezolizumab, which were developed by multinational corporations (55,56), three locally developed PD-1 inhibitors (camrelizumab, tislelizumab, and sintilimab) are also available in China (31,48,(57)(58)(59). 2) (9,67,68). Some of the trials were conducted only in China, and some were international multicenter clinical trials that involved Chinese sites (69).…”
Section: Current Nsclc Immunotherapy Landscapementioning
confidence: 99%
“…Mounting evidence from randomized controlled trials has confirmed that, compared with platinum-based chemotherapy, ICIs provide better clinical outcomes in patients with advanced NSCLC ( Table 2 ) ( 9 , 67 , 68 ). Some of the trials were conducted only in China, and some were international multicenter clinical trials that involved Chinese sites ( 69 ).…”
Section: Ici As First-line Therapy For Advanced Nsclcmentioning
confidence: 99%
See 2 more Smart Citations
“…Nowadays, immune checkpoint inhibitors (ICIs) have proven to be a major breakthrough achievement in cancer treatment in the past decade. Especially, ICIs have shown convincing efficacy and tolerable safety in monotherapies or combined treatments in NSCLC [ 5 , 6 ]. However, the objective response rate of ICIs is only about 17%, indicating that it could benefit only a limited subpopulation of patients [ 7 ].…”
Section: Introductionmentioning
confidence: 99%